A Security Community or a Game of Interests? Opportunities and Threats in Central Europe During a Time of Crisis - Gizicki, Wojciech (Roczniki Nauk Społecznych, 2024)
The war in Ukraine and the multidimensional crisis in Europe are adversely affecting the position, ability, and possibilities of cooperation in Central Europe. For the past 30 years, the Central European nations, despite their natural differences, have been able to engage in lasting cooperation to ensure their own and the region’s security. It seems that there has been a unique kind of cooperation for common interests, as Karl Deutsch puts it. Presently, we can see that, due to the decisions of voters, diverse interests, and the external position of the Central European nations, there are internal differences and divisions. In some cases, the region’s nations have a specific kind of personal game of interests. The article will attempt to outline the latest and most relevant matters that are high on the region’s agenda, particularly taking into account opportunities and threats.